Shakespeare, Survival, and the Seeds of Civilization in Emily St. John Mandel's Station Eleven. Issue 3 (January 2016) - Smith, Philip
Abstract : This paper will explore the role of Shakespeare in Emily St. John Mandel's post-apocalyptic novel Station Eleven. The following analysis will demonstrate that the text takes up and recontextualizes Shakespeare's depiction of religious, civil, and biological apocalypse, indicating a thematic continuation of Elizabethan apocalyptic works into the post-apocalyptic genre. Where Shakespeare's works imagine an apocalypse as a return to an earlier, more violent time, St. John Mandel depicts a world which has been returned to primitivism but is now recovering modernity. She also grapples with Shakespeare's recurring preoccupation with ephemerality in text and performance, and the possibility of survival through written and physical records. Station Eleven presents Shakespeare as containing the seed of civilization, an idea which is imbricated within the ideology of empire and restoration of British imperial power. The mobilization of Shakespeare is facilitated by simultaneous forward and backward momentum, a trope which is embodied both thematically and structurally within the text and embodies aspects of both American and British post-apocalyptic fiction.